Digestive hepatocholecyst anastomosis - Praderi, Raúl; Gómez Fossati, Carlos; Machado, Romeu; Ituño, Carlos; Guicheff, Vladimir; Davidenko, Nicolás; Liard, Washington (Cirugía del Uruguay, 1974)
Case material consists of 7 cases of hepatocholecysto digestive anastomosis performed in 5 patients with inoperable biliary cancers and 2 patients with jaundice caused by ganglionar metastases of digestive tumors ( colon and • stomach). This operation is resorted to in cases of necessity in arder to anastomose intrahepatic biliary tree to gal! bladder and the latter to the digestive tube in frozen hepatic pedicles. In lower pedicular cancers obstructing cystic duct, hepatovesicular anastomosis on Kehr's tube allows for hile flow into gal! bladder from which it is derived to jejunum, stomach and duodenum.